Initial Characterization of Low Molecular Weight Hydrocarbons in an Oil Sands Pit Lake - Han Bao; Chenlu Wang; Bridget S. H. Steven; Greg F. Slater (Earth, 2025)
Water-capped tailings technology (WCTT) is a strategy where oil sand tailings are sequestered within a mined-out pit and overlayed with a layer of water in order to sequester tailings with the aim that the resulting pit lake will support aquatic plants and organisms over time. The Base Mine Lake Demonstration (BML) is the first full-scale demonstration of a pit lake in the Athabasca Oil Sands Region (AOSR). In the BML, the release of methane from the fluid tailings influences several key processes, including the flux of greenhouse gases, microbial oxygen consumption in the water column, and ebullition-facilitated transport of organics from the fluid tailings to the lake surface. It is hypothesized that the residual low molecular weight hydrocarbons (LMWHCs) derived from diluent naphtha used during bitumen extraction processes are the carbon sources fueling ongoing microbial methanogenesis within the BML. The aims of this study were to identify the LMWHCs in the BML fluid tailings, to elucidate their sources, and to assess the extent of biogeochemical cycling affecting them. A headspace GC/MS analysis identified 84, 44, and 56 LMWHCs (C4–C10) present in naphtha, unprocessed bitumen ore, and fluid tailings, respectively. Equilibrium mass balance assessment indicated that the vast majority (>95%) of LMWHCs were absorbed within residual bitumen rather than dissolving into tailings pore water. Such absorbed compounds would not be readily available to in situ microbial communities but would represent a long-term source for methanogenesis. Chromatographic analysis revealed that most biodegradable compounds (n-alkanes and BTEX) were present in the naphtha but not in fluid tailings or bitumen ore, implying they are sourced from the naphtha and have been preferentially biodegraded after being deposited. Among the LMWHCs observed in bitumen ore, naphtha, and fluid tailings, C2-cyclohexanes had the highest relative abundance in tailings samples, implying their relatively high recalcitrance to in situ biodegradation.